Efficacy and safety of ombitasvir/paritaprevir/ritonavir and dasabuvir ± ribavirin for hcv in brazilian adults with advanced fibrosis - Pessoa, Mario G.; Ramalho-Madruga, José V.; Alves, Katia; Nunes, Estevão P.; Cheinquer, Hugo; Brandão-Mello, Carlos E.; Mendes-Correa, Maria C.; Ferraz, Maria L.; Ferreira, Paulo R. A.; Álvares-Da-Silva, Mário R.; Coelho, Henrique S.; Affonso-De-Araújo, Evaldo S.; et al. (Elsevier, 2018)
Introduction and aim. Approximately 650,000 people in Brazil have chronic hepatitis C virus (HCV) infection. We evaluated the safety and efficacy of ombitasvir (OBV)/paritaprevir (PTV)/ritonavir (r) plus dasabuvir (DSV) with/without ribavirin (RBV) in an openlabel multicenter phase 3b trial in treatment-naive or interferon (IFN) treatment-experienced Brazilian patients with advanced hepatic fibrosis (METAVIR F3/4) and HCV genotype (GT) 1 infection. Material and methods. All patients received coformulated OBV/ PTV/r daily + DSV twice daily (3-DAA). GT1a-infected patients received 3-DAA plus RBV for 12 weeks, except for prior pegIFN/ RBV nonresponders with cirrhosis who were treated for 24 weeks. GT1b-infected patients received 3-DAA alone (F3) or in combination with RBV (F4) for 12 weeks. The primary endpoint was sustained virologic response (HCV RNA < 15 IU/mL) at post-treatment Week 12 (SVR12). Results. The study enrolled 222 patients, 214 achieved an SVR12 (96.4%; 95% CI, 93.1-98.2%), one GT1a-infected patient experienced virologic breakthrough, six (5 GT1a) relapsed, and one was lost to follow-up. SVR12 was achieved in 111/ 112 (99.1%) GT1b-infected patients, including 42/43 (97.7%) noncirrhotic, and 69/69 (100%) cirrhotic patients; and in 103/110 (93.6%) GT1a-infected patients, including 44/46 (95.7%) noncirrhotic and 59/64 (92.2%) cirrhotic patients. Overall there was a low rate of serious adverse events (n = 6, 2.7%). One patient experienced a treatment-related serious adverse event and one patient discontinued treatment because of an adverse event. Discussion. The results confirm that the 3-DAA regimen with/without RBV is well tolerated and had a favorable safety profile and is efficacious in GT1-infected patients with advanced fibrosis (METAVIR F3/4).
Keywords: Advanced fibrosis; Chronic hepatits C; Direct-acting antivirals; Genotype 1